The Malaysian Government’s Actions in Improving and Protecting the Rights of Foreign Workers in Peninsular Malaysia (Journal of Governance and Development (JGD), 2016)
The rapid economic development has resulted in an influx of foreign workers in this country. Without their sweat, the construction of skyscraper buildings cannot be completed on time. low wages and their dedication in work make the employers prefer foreign workers compared to local workers. It is common for some employers to give bad treatment towards the foreign workers. Foreign workers have been denied the rights to wages, rest days, public holidays and other benefits under the law in Peninsular Malaysia. The objective of this research is to identify the actions of the Malaysian Government in improving and protecting the rights of foreign workers in Malaysia. This research used doctrinal research and the researchers used the primary and secondary data. The data comprise articles from journals, textbooks, and newspaper cutting. All the data collected have analysed descriptively and critically. The findings of the research showed that there have been violations of the rights of foreign workers in Peninsular Malaysia. The violation are as follows: violation of the right under a contract of service, violation of the right complaint against discrimination, violation of the right in dismissal, violation of the right in payment of wages, and violation in relation to working hours, rest day, public holidays and annual leave. The other violations of the right towards foreign workers are violation to safety, health and welfare at workplace which includes violation to basic rights, violation of the right to compensation and violation of right under the passport Act 1966. The researchers have identified the actions of the government in improving and protecting the rights of foreign workers in Peninsular Malaysia. The major actions taken by the Malaysian government are firstly, through administrative action, secondly, by improving and protecting the rights of foreign workers under relevant legislations, thirdly, by improving and protecting the right of foreign workers in safety and health at workplace, fourthly, through legislative actions, fifthly, through diplomatic actions and finally, indirectly through decisions of the courts.